Copper-Catalyzed Regioselective C–H Iodination of Aromatic Carboxamides - Wu, Chuanguang; Zhou, Hui; Wu, Qiaolin; He, Mina; Li, Pei; Su, Qing; Mu, Ying (Synlett, 2016)
A concise and efficient copper-catalyzed C–H iodination of 8-aminoquinoline-based aromatic carboxamides was reported. The reaction has the broad substrate scope and shows moderate to high yields, also offers other attractive advantages including simplicity of operation, compatibility with heteroarenes, and the use of low-cost copper catalyst. The new approach was further applied to cyanation of N-(quinolin-8-yl)benzamide, offering a potentially attractive alternative to the synthesis of aromatic nitriles.
Keywords: aryl halide; aromatic carboxamides; C–H halogenation; copper catalyst; heteroarenes; regioselective iodination